Analysis of microplastic content in milkfish (Chanos chanos) in the Domas Village aquaculture pond, Pontang District, Serang Regency, Banten Province - Safina, Salsabila Alya; Hermawan, Dodi; Aryani, Desy (Universitas Malikussaleh, 2025)
This research was conducted in Domas Village, Pontang District, Serang Regency, Banten Province, which is a milkfish farming pond. The purpose of this study was to analyze the abundance of microplastic particles in milkfish, identify the characteristics of microplastic particles in milkfish and identify the types of polymers that make up microplastics. This study aims to provide information about microplastics in milkfish in Domas Village which can be used as a development of science about microplastic pollution. The methods used in sampling are purposive sampling and descriptive analysis in identifying microplastics. The results showed that milkfish samples, sediment and water had been contaminated with microplastics of fiber, film and fragments with different abundances at each station. The highest abundance of microplastics in meat organs had a value of 14 particles/ind of film type at station 2, the highest abundance in water came from film type with a value of 5 particles/ml, and the highest abundance in sediment came from film type with a value of 6 particles/g. The results of the FTIR test conducted showed that there were 2 types of polymers, namely polycarbonate (PC) and acrylonitrile butadiene styrene (ABS). Keywords: FTIR; Microplastic; Milkfish